Dampak Hubungan Keluarga terhadap Penerimaan Diri Individu LGBT (Studi Kasus pada LGBT) - Rosalinda; Firman; Netrawati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This study aims to understand the role of the family in the formation of identity and self-acceptance of LGBT individuals, as well as its impact on behavior and mental health. This study uses a qualitative descriptive method with a case study on a respondent in city X. Data were collected through in-depth interviews. The results of the study indicate that lack of family attention and support, as well as negative influences from the social environment, including the use of the Grindr application, contribute to deviant behavior. Family disharmony, lack of role models from parents, and lack of early sex education are also identified as contributing factors. This study emphasizes the importance of the role of the family in shaping character, mentality, and mindset, especially related to sexuality, as well as the need for early sex education to prevent deviant behavior.